KAJIAN KEKUATAN KEJUT BIOKOMPOSIT SERAT SERABUT KELAPA SEBAGAI BAHAN YANG RAMAH LINGKUNGAN - Prasetyo, Nawanji; kristanto, Ari; Wibowo, Wibowo; Wijoyo, Wijoyo (Program Kreativitas Mahasiswa - Penelitian, 2013)
The purpose of this study was to investigate the effect of the weight fraction of coir fiber at 5 %, 15 %, 25 %, 35 % and 45 % of the strength of oil-polyester biocomposites shock. Examining cross-section of the test results in order to provide an analysis of the reasons for recommending the feasibility of coir fiber as a natural fiber composite materials that are environmentally friendly. The study was conducted with fiber coconut fiber, matrix type Unsaturated Polyester 157 BQTN, hardener metyl etyl ketone peroxide ( MEKPO ), alkali solution ( NaOH ), ethanol ( C2H5OH ) and H2O. The main equipment used in this study is a tool Charpy impact. From the test results showed that : Effect of treatment of coir fiber volume by immersion for 2 h at 35 % alkali solution is able to improve the strength of shock loads. The best specimens are those that contain fiber volume by 45 %, ie the shock force of 0.085 J/mm2. Based on the shock test the coir fiber is used as a viable alternative to composite reinforcing materials that are environmentally friendly.Â Keywords: Composites, coir fiber, Alkali